Ritual Slaughter: The Tradition of Pilot Whale Hunting on the Faroe Islands - Mamzer, Hanna Maria (Frontiers in Veterinary Science, 2021)
Faroese people consider grindadráp, hunting of pilot whales, as a part of their cultural heritage, but from the point of view of veterinary sciences and biology, the method of killing pilot whales is a form of a ritual slaughter that is performed on fully conscious animals aware of their circumstances. Pilot whales are social, intelligent, and communicative animals that demonstrate complex social behaviors. Therefore, this traditional whaling should be considered a procedure exposing the animals to a high level of distress. In the context of contemporary civilizational development and material welfare, the practice of whaling may appear to be an inadequate and cruel relic of the past. This text explores social and cultural issues caused by pilot whale hunts and presents and understanding of the term tradition and some perspectives of how traditions change. The specificity of pilot whales as a species is presented, setting a foundation for a discussion about hunting itself. The conclusion of the text discusses different social perceptions of grindadráp by presenting arguments for and against the hunting. This analysis includes a presentation of actions undertaken by the whale hunting opponents.